Role of Nepali Army in Promotion and Preservation of Nepalese Art, Culture, and Traditions - Gautam, Uddhav (Unity Journal, 2022)
The Nepali Army was founded initially as the Gorkha Army around 450 Years ago. Since its inception, the Nepali Army as the nation's largest organization has not only been ensuring our territorial integrity but has also been connecting multi-ethnic, multi-lingual, multi-religious, multi-cultural Nepalese society in a common thread by preserving its rich tangible and intangible cultural heritages along with the associated traditions. In this regard, this study predominantly illuminates the fact that modern-day Nepal has been shaped through the sacrifices of the Nepali Army and their histories are interwoven altogether. This research illustrates that the Nepali Army has been preserving and promoting Nepalese art, culture, and tradition for centuries both in times of peace and war. Despite socio-economic and political shifts in the nation's history over time, the Nepali Army has remained resolute in its spirit assimilating various cultural transplants within the organization promoting cultural relativism. Within this frame of reference, this study primarily aims to unfold major hurdles the Nepali Army is currently facing in the conundrum of operational and ceremonial duties along with the impacts of modern world issues, such as digitization and modernization. To fulfil objectives, this study follows a qualitative research methodology. It analyzes data collected from various primary and secondary sources and analyze it to draw out relevant inferences. I explore the military institution's roles to promote arts and cultures based on quantitative data with qualitative analysis.